Impact of smoking on immune feature and prognosis in unresectable stage III anaplastic lymphoma kinase positive non-small-cell lung cancer - Jiang, Ying; Zhang, Zhihui; Cao, Jianzhong; Duan, Jianchun; Zhang, Tao; Wang, Yu; Li, Weihua; Tan, Fengwei; Ying, Jianming; Bi, Nan (Frontiers in Oncology, 2026)
IntroductionSmoking is the primary risk factor for lung cancer, and 37% - 42% of patients with non-small-cell lung cancer (NSCLC) harboring anaplastic lymphoma kinase (ALK) mutation being smokers. Nevertheless, the specific impact of smoking on prognosis in patients with unresectable stage III ALK-positive NSCLC remains to be elucidated.MethodThis two-centric, retrospective cohort study included 48 patients with unresectable stage III ALK-positive NSCLC. Gene ontology (GO) enrichment analysis was conducted on data from 25 patients who underwent NGS. We further performed Gene Set Enrichment Analysis (GSEA) and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analysis to validate these findings, using the GSE31852 dataset (n = 34) patients from the Gene Expression Omnibus (GEO) database.ResultsIn these 48 patients, the median age was 55.2 (range, 33-80) years; approximately half of the patients were men (50.0%) and smokers (45.8%); 62.5% patients had IIIB stage disease; 33.3% patients initially received chemoradiation therapy (CRT). After a median follow-up of 49.02 (interquartile range [IQR], 35.84 - 62.03) months, CRT significantly improved the locoregional-free survival (LRFS, P = 0.012). Univariate and multivariate Cox regression analysis suggested that smoking was independent prognostic factors for poorer OS (univariate HR = 3.01, P = 0.049; multivariate HR = 3.92, P = 0.023). Compared with never-smokers, smokers exhibited a significantly inferior 5-year OS (51.9% vs. 78.9%, Log-rank P = 0.038). GO analysis revealed distinct biological processes and cell components between never-smokers and smokers. Validation in the GSE31852 dataset subsequently confirmed these findings and further highlighted the significant differences in immune cell regulation, including immune cell infiltration, differentiation, and interactions between never-smokers and smokers.ConclusionsIn patients with unresectable stage III ALK-positive NSCLC, CRT improved the disease control. Smokers exhibited a significantly poorer OS and DMFS, and may require more risk-adapted treatment strategies, such as the combination of CRT with upfront ALK TKIs. These findings suggest that smoking may adversely affect survival by modulating the tumor immune microenvironment.